THE EFFECT OF WORK ENVIRONMENT AND COMPETENCE ON EMPLOYEE PERFORMANCE THROUGH SATISFACTION WORK IN RESEARCH AND INNOVATION BODY MEDAN CITY REGION - Andre Masago Manik; Prihatin Lumbanraja; Parapat Gultom (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
Human resources are individuals who work as a driving force for an organization, both institutions and companies and function as an asset that must improve and develop their abilities so that they can provide good performance to realize the vision and mission that has been set. Matters regarding performance are very important, because performance is one of the most important measures of organizational quality. One of the factors that affect employee performance is the work environment and competence. In addition, job satisfaction is also an important aspect that affects employee performance. The purpose of this research is to analyze the effect of work environment and competency on employee performance through job satisfaction. This research was conducted at the Regional Research and Innovation Agency (Brida) Medan City with a sample of 43 respondents who are permanent employees at the Regional Research and Innovation Agency (Brida) Medan City. The data were analyzed using descriptive analysis and SEM (Structural Equation Model) analysis. The results showed that directly the environment had a positive and significant effect on job satisfaction, content had a positive and significant effect on job satisfaction, the work environment had a positive and significant effect on employee performance, content had a positive and significant effect on employee performance , and job satisfaction had a positive and significant effect on employee performance. indirectly,